2021
DOI: 10.3390/nano11010089
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Antifouling Characteristics of Helicene—Graphene Films

Abstract: Herein, we describe interfacially-assembled [7]helicene films that were deposited on graphene monolayer using the Langmuir-Schaefer deposition by utilizing the interactions of nonplanar (helicene) and planar (graphene) π–π interactions as functional antifouling coatings. Bacterial adhesion of Staphylococcus aureus on helicene—graphene films was noticeably lower than that on bare graphene, up to 96.8% reductions in bacterial adhesion. The promising bacterial antifouling characteristics of helicene films was att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…This strategy is particularly designed for the deposition of rigid monolayers and protein films on a solid substrate. The LS technique was reported as useful in culturing stem cells, , preparation of the bacterial antifouling surface, and immobilization of enzymes . Apart from versatility, LB and LS techniques offer controllable thickness of the film and the deposition at thermodynamically stable conditions .…”
Section: Introductionmentioning
confidence: 99%
“…This strategy is particularly designed for the deposition of rigid monolayers and protein films on a solid substrate. The LS technique was reported as useful in culturing stem cells, , preparation of the bacterial antifouling surface, and immobilization of enzymes . Apart from versatility, LB and LS techniques offer controllable thickness of the film and the deposition at thermodynamically stable conditions .…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30][31][32][33] Additionally, some efforts have also been made for the development of helicene-based bioapplications. [34,35] For example, Tanaka et al found that (P)bis(dimethylaminomethyl)helicene displayed chiral selection in binding to left-handed Z-form DNA [36] while Lacour and co-workers investigated the mitochondria-targeted imaging abilities of cationic helicenes and [4]helicene-squalene nanoassemblies in living cells and Chlamydomonas. [37,38] Nevertheless, helicene-based bioimaging is still rarely explored.…”
mentioning
confidence: 99%